PENGARUH PENDIDIKAN KESEHATAN TERHADAP PERILAKU PERSONAL HYGIENE SAAT MENSTRUASI PADA SISWI SMP DAN SMA DI YAYASAN PASRAMAN GURUKULA BANGLI - Laras, I Dewa Ayu Alit Maharani; Damayanti, Made Rini; Pramitaresthi, I Gusti Ayu (Coping: Community of Publishing in Nursing, 2020)
Personal hygiene behavior during menstruation is one of actions that can be done to reduce reproductive health problems. The effectiveness of personal hygiene behavior can be improved by giving health education. This study aimed to determine the effect of health education on personal hygiene behavior during menstruation among middle and high school students at Pasraman Gurukula Bangli Foundation. This study was quasi-experimental with one group pretest-posttest design. Sample of this research was 43 respondents that selected by total sampling technique. Health education as an intervention was given by lecture and demonstration methods, four times with a duration of 60 minutes on each meeting. Data on personal hygiene behavior during menstruation were collected by questionnaire of knowledge, attitudes, and behaviors that had been tested for validity and reliability. Personal hygiene behaviors data were analyzed using paired t-test and Wilcoxon test. The result shows that p value = 0.001; ? <0.05, so it means that there is an effect of health education on knowledge, attitudes, and personal hygiene behaviors among middle and high school students at Bangli Pasraman Gurukula Foundation. It is suggested for students to apply personal hygiene well in accordance with the health education material that has been given with existing facilities and infrastructure and further researchers are expected to be able to use observation form to observe students? behaviors in carrying out personal hygiene during menstruation.